2008
DOI: 10.1073/pnas.0806526105
|View full text |Cite
|
Sign up to set email alerts
|

T antigen mutations are a human tumor-specific signature for Merkel cell polyomavirus

Abstract: Merkel cell polyomavirus (MCV) is a virus discovered in our laboMerkel cell carcinoma ͉ pRB interaction ͉ viral integration ͉ virus replication ͉ helicase M erkel cell carcinoma (MCC) is an aggressive skin cancer associated with sun exposure and immunosuppression (1, 2). Using digital transcriptome subtraction, we recently identified Merkel cell polyomavirus (MCV) as a novel polyomavirus integrated into the genome of MCC tumors (3, 4). The close association between MCV and MCC has been confirmed by others (5).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

29
908
1
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 639 publications
(961 citation statements)
references
References 37 publications
29
908
1
6
Order By: Relevance
“…Merkel cell polyomavirus has a large T antigen LXCXE domain that, when expressed, binds directly to retinoblastoma protein. 45 Several lines of evidence have suggested We found that polyomavirus-negative cases with little or no detectable polyomavirus by sensitive real-time polymerase chain reaction had truncating, nonsense RB1 mutations. Even though two of the five polyomavirus-positive cases showed RB1 deletions (one case with a deletion and one with copy number variation), there were no single-nucleotide variation truncating nonsense mutations within polyomavirus-positive cases.…”
Section: Discussionmentioning
confidence: 79%
“…Merkel cell polyomavirus has a large T antigen LXCXE domain that, when expressed, binds directly to retinoblastoma protein. 45 Several lines of evidence have suggested We found that polyomavirus-negative cases with little or no detectable polyomavirus by sensitive real-time polymerase chain reaction had truncating, nonsense RB1 mutations. Even though two of the five polyomavirus-positive cases showed RB1 deletions (one case with a deletion and one with copy number variation), there were no single-nucleotide variation truncating nonsense mutations within polyomavirus-positive cases.…”
Section: Discussionmentioning
confidence: 79%
“…It was the first human pathogen discovered through nondirected transcriptome sequencing using an approach called digital transcriptome subtraction. MCV infection is nearly ubiquitous among human adults, and MCC tumors arise as rare biological accidents after prolonged infection in which the MCV genome becomes integrated into the host cell genome and mutations to the 3′ MCV LT gene clonally occur that eliminate the carboxyl terminus T antigen helicase domain (12)(13)(14). The viral integration and T antigen mutations that occur in tumors are incompatible with transmissible MCV replication, and tumors represent a biological dead end for the virus.…”
mentioning
confidence: 99%
“…Merkel cell polyomavirus in Merkel cell carcinoma displays clonal integration, high viral copy number, and tumorspecific mutations of large T antigen resulting in incapacity to replicate. 5,17,18,32 Furthermore, in vitro studies support a role for Merkel cell polyomavirus T antigens, especially small T antigen, in transformation and cell survival. 5 Most studies have reported that a significant minority of Merkel cell carcinoma lack detectable Merkel cell polyomavirus, 5 raising the question of how Merkel cell polyomavirus-negative tumors might differ from Merkel cell polyomavirus-positive tumors.…”
Section: Discussionmentioning
confidence: 96%
“…5 Merkel cell polyomavirus associated with Merkel cell carcinoma displays tumor-specific mutations or deletions in large T antigen which render the virus replication deficient, a common characteristic of oncogenic viruses. 5,18 Although numerous assays for Merkel cell polyomavirus detection have been reported, PCR targeting small T antigen and/or the 5' region of large T antigen is commonly used and highly sensitive. [19][20][21] Although present in the majority of Merkel cell carcinoma, Merkel cell polyomavirus has not been commonly observed in other malignancies.…”
mentioning
confidence: 99%